Zapobieganie niepełnosprawności intelektualnej w świetle rozważań Amerykańskiego Stowarzyszenia Niepełnosprawności Intelektualnej i Rozwojowej (AAIDD) - Kopec, Danuta (Kultura-Społeczeństwo-Edukacja, 2012)
The long-awaited handbook by the special pedagogy educators issued by the Committee on Terminology and Classi cation of the American Association on Intellectual and Developmental Disabilities (Schalock et al, 2010) appeared nally in 2010. This article discusses the way of understanding the prevention of intellectual disability represented in the aforementioned handbook which is an expression of the position of the AAIDD. The analysis embraces these forms of intellectual disability for which the reference point is the early interpersonal interaction between the parent/guardian and the child at intellectual disability risk or the child with intellectual disability. These are simultaneously understood by the AAIDD as forms of support for parents and/or guardians of a child threatened with intellectual disability or a child with intellectual disability. The article concludes with ndings drawn from the presented material.